Amaranth-alginate hydrogels: rheological, textural, and sensory properties for gluten-free noodles - Tanja Lux; Julia Krapf; Frederike Reimold; Annekathrin Lochny; Adam Erdoes; Eckhard Floeter (Future Foods)
Gluten-free products are receiving growing attention, with amaranth, a nutrient-rich pseudocereal widely used in their formulation. Due to the absence of gluten, hydrocolloids such as alginates are often added to enhance structure and texture. This study examines the impact of different flour-water ratio and alginate addition on the functional, rheological, and sensory properties of amaranth-based hydrogels. Pregelatinized amaranth flour (AS) was used to prepare suspensions with sodium alginate (ASA) and calcium-induced gelation applied to create strand-formed noodles (AN). Optimizing water availability was crucial in shaping the mechanical properties and gel structure. SEM analysis revealed that interactions between gelatinized amylose and alginate compacted the gel matrix, enhancing strength and stability. Texture analysis showed a strong negative correlation (r = -0.81) between gel stiffness and cutting force. Sensory testing indicated that higher water content improved texture smoothness and flavor neutrality. Optimal flour-water ratios (1:6, 1:8, 1:10) produced firm, cohesive noodles with desirable mouthfeel and minimal retrogradation. Overall, this work demonstrates the potential of pregelatinized amaranth flour and alginate to create high-quality gluten-free noodles with customized sensory and structural attributes, offering valuable insights for future product development.